Incidence of haemorrhage after tonsillectomy (Bangladesh Journal of Otorhinolaryngology, 2012)
Tonsillectomy is probably the most common operation performed by an Otolaryngologist. One of the most significant complications is post-operative haemorrhage. Episodes of post tonsillectomy haemorrhage are unpredictable and sometimes life threatening. The aim of the present study was to find out the incidence of reactionary haemorrhage after tonsillectomy. A prospective study was conducted at Shaheed Shamsuddin Ahmed Hospital, Sylhet from April 2010 to March 2011. We had selected 112 cases undergoing tonsillectomy. Tonsillectomy was done by cold steel dissection technique and bipolar diathermy haemostasis. Post operatively every patient was treated with pain killer (diclofenac sodium and paracetamol), antibiotics (amoxicillin and cloxacillin) and hydrogen peroxide mouth wash. Postoperative follow-up was done till the tonsillar fossa healed. The incidence of reactionary haemorrhage was 2.68%, primary and secondary haemorrhage was 0%. In our series haemorrhage (2.68%) was higher than that reported in most publications and may be due to inadequate per-operative haemostasis. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10415  Bangladesh J Otorhinolaryngol 2012; 18(1): 55-58